Wurmkos : tana. - Museo d'Arte Contemporanea di Villa Croce Genova; Bordone, Simona; Borzani, Luca; Campanella, Pasquale; De Battè, Brunetto; Marasco, Emilia; Scacchetti, Paolo; Serrati, Francesca; Solimano, Sandra (Genova : Museo d'Arte Contemporanea di Villa Croce, 2003)
Wurmkos ; Abate, Susanna ; Campanella, Pasquale ; Caserta, Caterina ; Carrera, Monica ; De Robertis, Isabella ; Bartolomeo, Angela Di ; Fede, Salvatore ; Longari, Elisabetta ; Lovaglio, Samuele ; Perrone, Andrea ; Russo, Antonio ; Santoro, Nicola ; Valente, Antonio ; Almeoni, Piero ; Cravera, Alessandro
bibliog. p.32
Italiaans
Exhibition. Wurmkos : tana. Museo d'Arte Contemporanea di Villa Croce Genova. 2002-10-30. 2003-01-26
boek